The effect of country of origin on current foreign students' intention to enrol in Islamic Banking and Finance (IBF) program in Malaysia - Said, Boumaali (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
This study explores the effect of country of origin on current foreign students' intention to enrol in Islamic Banking and Finance (IBF) programme in Malaysia. A quantitative approach is applied whereby data were collected via the distribution of 300 structured questionnaires to foreign students in Malaysia. This study proposes a conceptual model based on the factors of Theory of Planned Behaviour (TPB) with new additional variables. It investigates the direct impact of the TPB factors Attitude toward Behaviour (AtB), Subjective Norms (SN) and Perceived Behavioural Control (PBC), with a new factor labelled Country of Origin (COO) on the current students' intention to enrol in IBF programme in Malaysia. To test factor validity and goodness of the proposed model, factor analysis and multiple regressions were applied. The findings reveal that country of origin and subjective norms contribute significantly to students' intention whereas, attitude toward behaviour and perceived behavioural control insignificantly affect students' intention to enrol in IBF programme in Malaysia. These findings are valuable for marketing managers and Malaysian Higher Education Institution (MHEIs) who are seeking to attract foreign students to Malaysia to pursue further studies.